2006
DOI: 10.1158/0008-5472.can-05-4184
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for Independent Origin of Multifocal Neuroendocrine Tumors of the Enteropancreatic Axis

Abstract: Neuroendocrine tumors of the enteropancreatic axis are often multifocal. We have investigated whether multifocal intestinal carcinoid tumors and multifocal pancreatic endocrine tumors arise independently or whether they originate from a single clone with subsequent intramural or intrapancreatic spread. Twenty-four cases, including 16 multifocal intestinal carcinoid tumors and eight multifocal pancreatic endocrine tumors, were studied. Genomic DNA samples were prepared from 72 distinct tumor nodules using laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…37 The most consistently informative marker of the clonal composition of neoplasm in female subjects is the nonrandom pattern of X-chromosome inactivation. 26,29 Polyclonal proliferative lesions in female patients are composed of cells with different origins and randomly inactivated X-chromosomes will be identified within them, while neoplasms arising from a single clone are composed of cells in which the same X-chromosome is inactivated. 26,29,38,39 In our study, one inverted papilloma showed nonrandom inactivation of X-chromosomes, suggesting that inverted papillomas arise from a single progenitor cell and supporting the clonal process of inverted papilloma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 The most consistently informative marker of the clonal composition of neoplasm in female subjects is the nonrandom pattern of X-chromosome inactivation. 26,29 Polyclonal proliferative lesions in female patients are composed of cells with different origins and randomly inactivated X-chromosomes will be identified within them, while neoplasms arising from a single clone are composed of cells in which the same X-chromosome is inactivated. 26,29,38,39 In our study, one inverted papilloma showed nonrandom inactivation of X-chromosomes, suggesting that inverted papillomas arise from a single progenitor cell and supporting the clonal process of inverted papilloma.…”
Section: Discussionmentioning
confidence: 99%
“…26,28 The clonality of the samples was evaluated on the basis of a polymorphism of the X-linked human androgen receptor gene (HUMARA) locus. 26,[28][29][30] This technique is dependent on digestion of DNA with the methylation-sensitive restriction enzyme HhaI, PCR amplification of the HUMARA locus and the detection of methylation at this locus. With this method, only the methylated HUMARA allele is amplified by PCR.…”
Section: Detection Of X-chromosome Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Briefly, the cells of interest are identified and thermoplastic transfer film is placed over the area of interest with the film on an uncoverslipped, uncharged glass slide. A laser is activated and passes through the transfer film.…”
Section: Tissue Samples and Microdissectionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) was used to amplify genomic DNA at seven specific loci on six different chromosomes: 7q31.1 (D7S2554); 8q24 (D8S263); 9p21 (D9S157, D9S161); 13q14 (D13S319); 17p13 (TP53); 20q12 (D20S108). 6 PCR was performed in a 25 ml volume containing 0.8 mCi of a-32 P-labeled dATP, 2 mM of mappair primers, 0.3 mM of dNTP, 0.65 U of iTaq DNA Polymerase (Bio-Rad Lab, Hercules, CA, USA). PCR amplification has an initial denaturation step of 951C for 5 min, followed by 35 cycles at 951C for 30 s, at 581C for 30 s, and at 721C for 30 s, and then followed by a single final extension step at 721C for 7 min.…”
Section: Detection Of Lohmentioning
confidence: 99%